Application of whey of Mozzarella di Bufala Campana fermented by lactic acid bacteria as a bread biopreservative agent. (27th May 2021) - Luz, Carlos; Quiles, Juan M.; Romano, Raffaele; Blaiotta, Giuseppe; Rodríguez, Lorena; Meca, Giuseppe
Summary: A total of nine isolated lactic acid bacteria (LAB) from tomato and sourdough with antifungal activity were employed to revaluate the whey of Mozzarella di Bufala through the fermentation process for 72 h at 37 °C. Then, the fermented whey (BWF) was characterised and used as biopreservative in bread formulation. L . plantarum TR7 and L . plantarum TR2 strains showed average lactic acid concentration in BWF of 13.8 g L −1 . Also, the bread volatile organic compounds (VOC) analysis showed an increase in hexanal, benzeneacetaldehyde, benzaldehyde and pyrazine tetramethyl when using BWF as ingredient. Moreover, the DPPH‐inhibitory activity of bread with BWF extract also reflected a 33% rise in comparison with control bread. The application of BWF as a biopreservation agent in bread showed an increase in shelf life compared with bread with 0.3% calcium propionate and bread control for 2 and 15 days, respectively. BWF can be used as an interesting biopreservation strategy of bread. Abstract : Fermentation of Mozzarella di Bufala Campana whey by selected lactic acid bacteria with antifungal activity, identification of the bioactive compounds responsible of the antifungal activity and the application of whey fermented as a bio‐preservative agent for the shelf life improvement of bread.